Cis-regulation of the amino acid transporter genes ZmAAP2 and ZmLHT1 by ZmPHR1 transcription factors in maize ear under phosphate limitation. (3rd March 2021) - Wang, Ruifeng; Zhong, Yanting; Liu, Xiaoting; Zhao, Cheng; Zhao, Jianyu; Li, Mengfei; Ul Hassan, Mahmood; Yang, Bo; Li, Dongdong; Liu, Renyi; Li, Xuexian
Abstract : Low phosphate leads to sparse kernel setting and reduced accumulation of nitrogen metabolites and ZmPHR1 transcription factors serve as direct linkers of phosphorus and nitrogen nutrition in maize. Abstract: Phosphorus and nitrogen nutrition have profound and complicated innate connections; however, underlying molecular mechanisms are mostly elusive. PHR1 is a master phosphate signaling component, and whether it directly functions in phosphorus–nitrogen crosstalk remains a particularly interesting question. In maize, nitrogen limitation caused tip kernel abortion and ear shortening. By contrast, moderately low phosphate in the field reduced kernels across the ear, maintained ear elongation and significantly lowered concentrations of total free amino acids and soluble proteins 2 weeks after silking. Transcriptome profiling revealed significant enrichment and overall down-regulation of transport genes in ears under low phosphate. Importantly, 313 out of 847 differentially expressed genes harbored PHR1 binding sequences (P1BS) including those controlling amino acid/polyamine transport and metabolism. Specifically, both ZmAAP2 and ZmLHT1 are plasma membrane-localized broad-spectrum amino acid transporters, and ZmPHR1.1 and ZmPHR1.2 were able to bind to P1BS-containing ZmAAP2 and ZmLHT1 and down-regulate their expression in planta . Taken together, the results suggest that prevalence of P1BS elements enables ZmPHR1s to regulate a large number of low phosphate responsive genes. Further, consistent with reduced accumulation of free amino acids, ZmPHR1s down-regulate ZmAAP2 and ZmLHT1 expression as direct linkers of phosphorus and nitrogen nutrition independent of NIGT1 in maize ear under low phosphate.